Kinetic study for adsorption of ?-naphtholphthalein onto silica gel surface-imprinted polymer and non-imprinted polymer - Gundogdu, Niluefer; Coskun, Mehmet (Taylor & Francis Inc, 2016)
In this study, the molecular imprinting polymer (MIP) was prepared using -naphtholphthalein as a template, 2-(diethylamino)ethyl acrylate as a functional monomer and ethylene glycol dimethacrylate as a crosslinking agent by aid of free radical polymerization onto surfaces of vinyltrimethoxysilane modified silica gel. The MIP was extracted with acetonitrile for overnight to remove the template molecule from the MIP. Non-imprinted polymer (NIMP) was synthesized using the same materials except -naphtholphthalein as template molecule. -Naphtholphthalein adsorption on surfaces of the both polymer was studied at three different temperatures (19 degrees C, 25 degrees C and 35 degrees C). It was observed that the adsorption capacity increased with increasing temperature and with time. The time required to reach the equilibrium for two polymers and all temperature was accepted to be nearly 6h. The saturated adsorption amounts at the equilibrium were found as 120mg/g, 123mg/g and 127mg/g at 19 degrees C, 25 degrees C and 35 degrees C, respectively, for MIP, and 78mg/g, 98mg/g and 120mg/g at 19 degrees C, 25 degrees C and 35 degrees C, respectively, for NIMP. The mechanism of adsorption of -naphtholphthalein onto MIP and NIMP is nearly appropriate to pseudo-first-order kinetic model with an activation energy of 11.63kJ/mol for MIP, and 23.69kJ/mol for NIMP. Thermodynamic parameters of activated complex in the adsorption process showed that the adsorption was carried out with an endothermic activation enthalpy, large negative entropy changes and the positive values of G* that the adsorption processes is not favorable.
Keywords: alpha-Naphtholphthalein; molecular imprinting; adsorption; kinetics; activation parameters